Vehicle Traffic Safety Assessment at the Intersection of Highways and Railways at the Same Level - Kurhan, M. B; Kurhan, D. M; Husak, M. A; Havrylov, M. O; Luzhytskyi, O. F (Science and Transport Progress, 2022)
Purpose. The purpose of the study is to assess the state of vehicle traffic safety at the intersection of highways and railways at the same level, as well as the subsequent development of measures to improve road traffic safety at railroad crossings. Assessing the degree of road traffic safety at railway crossings is one of the main tasks of both the road operation service and railway transport services. Therefore, it is advisable to implement a system for assessing the level of safety at railroad crossings, which is necessary to identify dangerous areas and develop measures to improve traffic conditions on them. Methodology. In order to obtain initial data and methods of assessing the state of vehicle traffic safety at the intersection of highways and railways at the same level, the authors conducted a review of the world literature on the topic of the study, as well as monitoring the safety of vehicle traffic at the intersection of highways with railway tracks. On the basis of the various methodological approaches analysis, the method of the final accident rate was used, which makes it possible to assess the state of safety as a result of the modernization or new design decisions, that is, in the absence of data on road accidents. Findings. It was found that according to the final coefficient of railway accident rate, crossings can be classified into one of four classes: safe, low-risk, dangerous, very dangerous. The issue of reducing the risk of an accident at the interaction of railway and road transport has been studied. Originality. Scientific approaches to evaluating the safety of vehicle movement at the intersection of highways and railways have gained further development, at the same level as the calculation of accident coefficients and danger indicators based on the data of the AIS Pereizd subsystem, which is being implemented on the railways of Ukraine. Practical value. The obtained results will be useful for carrying out measures to increase the safety of traffic through railway crossings, especially in the directions of the introduction of high-speed train traffic. The use of the AIS Pereizd automated information subsystem will allow using the method of the final accident rate and evaluating the safety of rail transport and motor vehicles in the area of railway crossings without additional labor costs.